Effect of Insulin on Visuo-Spatial Memory and Histology of Cerebral Cortex in the Presence or Absence of Nitric Oxide Inhibition (Nigerian Journal of Physiological Sciences, 2021)
Summary: Insulin has emerged from its traditional ‘peripheral’ glucose-lowering function to become increasingly regarded as a brain hormone that controls a wide range of functions including learning and memory. Insulin action on learning and memory is linked to nitric oxide (NO) signalling, but its effects on memory and histology of cerebral cortex in conditions of varied NO availability is unclear. This research sought to determine the effect of insulin on visuo-spatial learning, memory and histology of cerebral cortex during NO deficiency. Twenty-four mice weighing 21-23 g, were divided into four groups (n = 6) and treated daily for seven days with 0.2 ml distilled water subcutaneously (s.c.) (control), 10 I.U/kg insulin s.c., 10 I.U/kg insulin + 50 mg/kg L-NAME intraperitoneally (i.p.), and 50 mg/kg i.p. L-NAME s.c., respectively. The 3-day MWM paradigm was used to assess memory. Brain tissue was examined for histological changes. There was no significant difference between day 1 and day 2 latencies for all the groups. The mice in all (but L-NAME) groups spent more time in the target quadrant, and the difference was significant within but not between groups. There was significant reduction in number of platform site crossings (4.83 ± 0.5, 0.67 ± 0.3, 0.50 ± 0.3 and 0.50 ± 0.3 for control, insulin, insulin+L-NAME and L-NAME groups, respectively) in all the groups compared to control. Normal histology of the cortex and absence of histological lesions were observed in brain slides of control and treatment groups. It was concluded that insulin administration impairs visuo-spatial memory to a greater extent in the presence of NO block, and to a lesser extent in the absence of NO block. Nitric oxide has a role in insulin-induced memory impairment. Insulin administration in the presence or absence of NO block had no effect on histology of cortex.